Halal certification in Indonesia; history, development, and implementation - Hayyun Durrotul Faridah (Universitas Airlangga, 2019)
Indonesia's population with a Muslim majority (87.18%) makes the need for halal products very large. There is a need for halal product guarantees for products entering or circulating in Indonesia. Halal guarantee in Indonesia is regulated by the Government through legislation. The halalness of a product can be determined by conducting halal certification by inspecting the product from the selection of raw materials, the production process, to the final product. The halal certification process in Indonesia has been developing. This study aims to describe the history, development, and implementation of halal certification in Indonesia, one of which is before and after the issuance of law on Halal Product Guarantee (Halal Law). Initially, halal certification in Indonesia was taken over by the Majelis Ulama Indonesia (MUI) which is a civil society movement that has the support of the state. But after the issuance of the Halal Law, the authority for halal certification was transferred to the Badan Penyelenggara Jaminan Produk Halal (BPJPH) which is an independent state institution under the Ministry of Religion of the Republic of Indonesia. This was also followed by several changes in several policies related to halal certification. Halal certification which was initially voluntary and does not yet have strong legal legitimacy has now become mandatory for business actors. Implementation of the Halal Law began on October 17, 2019, and will be carried out in stages. In the implementation effort, there needs to be a good collaboration between the government, business actors, and the community.